Tarīqatu Hypnoteaching li Tarqiyyati Mahārah Al-Kalām Laday Thalabati SMAINUS Malang - A'yunin Aditya Fajrin (INAIFAS PRESS, 2023)
A hypnoteaching method is needed to attract student learning interest. This study aimed to determine. The aim of this research was to determine the ability of student's speaking skills before and after the application of the hypnoteaching method and also to determine the effectiveness of the hypnoteaching method in improving students’ speaking skills in Arabic SMAINUS Malang. The research method used an experimental method with the type of Pre-Experimental Design One Group Pre-test Post-test. According to the results by using a comparison test of the two dependent variables. The researcer used the paired sample t test and comparing the t table with t arithmetic, the researcher obtained result that the significance value was 0.000 <0.05 and the t table value was 2.059 and t count was 13,22 showed 2,059 < 13,22 which meant t table < t count that H0 was rejected and Ha was accepted. It concludes that there was a significant difference from the average value of the pre-test and post-test so that the hypnoteaching method is effectively used in Arabic learning to improve the speaking skills of the students of SMA Islam Nusantara Malang.